Branched‐chain amino acid‐enriched nutrient increases blood platelet count in patients after endoscopic injection sclerotherapy. (15th March 2016) - Furuichi, Yoshihiro; Imai, Yasuharu; Miyata, Yuki; Sugimoto, Katsutoshi; Sano, Takatomo; Taira, Junichi; Kojima, Mayumi; Kobayashi, Yoshiyuki; Nakamura, Ikuo; Moriyasu, Fuminori
Abstract : Aim: Protein and energy malnutrition is a severe problem for patients with liver cirrhosis (LC) and fasting often induces starvation which is a vitally important outcome. Dietary restriction is essential for endoscopic injection sclerotherapy (EIS) in patients with risky esophageal varices, thereby creating the possible exacerbation of nutritional state and inducing liver dysfunction. Whether EIS induces nutritional deficiency in LC patients and the effects of branched‐chain amino acid (BCAA)‐enriched nutrient are prospectively investigated. Methods: A total of 61 LC patients were randomly divided into an EIS monotherapy group (non‐BCAA group, n = 31) and an EIS combined with BCAA therapy group ( n = 30). Platelet count, blood chemistry and somatometry values were prospectively measured at five time points. Results: The platelet counts before treatment were at the same level in both groups ( P = 0.72). Three months after treatment, the counts decreased in the non‐BCAA group; however, they increased in the BCAA group ( P = 0.019). Body mass index, triceps skin fold thickness and arm muscle circumference significantly decreased in both groups. The BCAA and tyrosine ratio value increased only in the BCAA group ( P < 0.01). The skeletal muscle volume measured by InBody720 significantly decreased in the non‐BCAA group ( P < 0.001). Conclusion: EIS induced protein‐energy malnutrition, however, skeletal muscle volume was maintained by taking BCAA. Administration of BCAA had some effect in maintaining the nutritional state, and may improve the platelet count. Taking a greater amount of nutrients and shorter dietary restriction period or hospitalization was desirable.